Literature Review of Collaborative Learning Strategies Based on Digital Education Innovation in Indonesia - Susiana, Alma; Priyatin, Desi (Generate Digital Publishing, 2025)
Objective: This study aims to explore the effectiveness and potential of collaborative learning strategies that integrate digital education innovations in the context of Indonesia's evolving digital education landscape. Research Design & Methods: A systematic literature review was conducted by selecting and analyzing ten peer-reviewed research articles published between 2020 and 2025. These articles were examined to identify trends, outcomes, and factors influencing digital-based collaborative learning strategies across different levels of education. Findings: The findings reveal that digital technologies play an important role in facilitating interactive, flexible, and personalized learning experiences. Collaborative digital tools such as Google Classroom, Quizizz, Flipbook Digital, MathTrail, video conferencing platforms, gamification apps, and educational podcasts have been shown to increase student engagement, strengthen group communication, and deepen conceptual understanding. The success of these strategies is influenced by appropriate platform selection, increased digital literacy among teachers and students, and pedagogical design that promotes meaningful and sustained interactions. Implications & Recommendations: To optimize the impact of digital collaborative learning strategies, it is important to invest in teacher training programs that focus on technological proficiency and pedagogical innovation. Policymakers and educational institutions should support infrastructure development and ensure equitable access to digital resources at all levels of education. Contribution & Value Added: This study contributes to the body of knowledge by providing a synthesized overview of how digital innovation supports collaborative learning in Indonesia. The study highlights practical tools and strategic factors that can guide educators, researchers, and decision-makers in implementing effective digital learning environments.